The role of lower body kinematics in optimising trunk dynamics and ball speed during the field hockey drag-flick - Ladru, B. J.; Tak, I.; Kortekaas, B.; Gijssel, M.; Kerkhoffs, G.; Langhout, R. (Sports Biomechanics, 2026)
Timing and coordination of body kinematics are crucial for drag-flick performance in field hockey. This study aimed to clarify how coordination between the lower limbs and trunk contributes to effective energy transfer by (1) comparing lower body and trunk kinematic patterns between senior and junior national-level players, (2) examining whether peak kinematic values and keypoints occur in temporal synchrony, and (3) determining whether lower body peak kinematics predict trunk deceleration and ball speed. Kinematic data and ball speed were collected from 57 players (9 senior, 48 junior) from the Royal Dutch Hockey Federation using a 3D motion capture suit (240 Hz) and radar gun. Senior players achieved significantly higher ball speeds and shorter flick phases, associated with more synchronised timing of peak movements and keypoints. Specifically, left foot touchdown (LFT) aligned with trunk acceleration onset, while onset of right wrist flexion (ORWF) corresponded with trunk deceleration onset. The lead leg acted as a braking mechanism converting linear to angular momentum of the trunk, while the trail leg contributed to propulsion and trunk deceleration. Junior players showed delayed peak kinematics and reduced synchronisation. These findings highlight the role of lower limb and trunk mechanics in optimising drag-flick performance through targeted training.